A Study on the Changes in Seawater Quality Due to Dumping of Trenching Materials - Gita Oktarina Eka Putri; Marlon Ivanhoe Aipassa; Henny Pagoray (Indonesian Journal of Global Health Research, 2025)
The dumping of trenching materials in offshore areas poses a potential risk to environmental quality and requires proper management to prevent disruption of ecosystem balance. Objective: This study aims to analyze changes in seawater quality, focusing on key parameters such as Total Suspended Solids (TSS), Dissolved Oxygen (DO), Ammonia (NH₃), Orthophosphate (PO₄-P), and Oil and Grease. Method: This study employed a quantitative descriptive research design aimed at assessing marine water quality. Primary data were collected through direct seawater sampling at three observation points in the coastal waters of Tanjung Jumlai, Penajam District, North Penajam Paser Regency. Seawater sampling was conducted using a Horizontal Water Sampler to ensure representative sample collection from each location.The collected samples were subsequently analyzed in a laboratory to determine the concentrations of five key water quality parameters. The results were then compared with baseline conditions and the marine water quality standards as stipulated in Government Regulation of the Republic of Indonesia No. 22 of 2021. Based on the laboratory results, the Marine Water Quality Index (IKAL) was calculated, and the water quality category was determined in accordance with the Minister of Environment and Forestry Regulation No. 27 of 2021.Results: "The analysis results showed an increase in TSS and ammonia levels, while DO slightly decreased after the dumping activity; however, these values remained below the quality standards. In contrast, orthophosphate and oil and grease levels increased beyond the permissible limits. Orthophosphate concentrations ranged from 0.020 to 0.030 mg/L, exceeding the quality standard of 0.015 mg/L, likely due to the release of nutrients contained in the sediments. Oil and grease concentrations reached 1.7 mg/L at all three observation sites, surpassing the standard of 1 mg/L, primarily due to vessel and heavy equipment operations during the dumping process. The rise in phosphorus and oil and grease levels serves as an early indicator of environmental pressure on marine waters and poses a risk of reducing aquatic biodiversity. Therefore, regular environmental quality monitoring is necessary to prevent more severe impacts. Although the Marine Water Quality Index decreased after the dumping activity, it remained within the range of 70–90, classified as 'good'.